THE CORRELATION BETWEEN STUDENTS’ SPEAKING ANXIETY AND THEIR SPEAKING PERFORMANCE IN AN EFL CONTEXT - Rahma Faridila Amaliah (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2019)
Numerous studies have been conducted in investigating the role of foreign language speaking anxiety on students’ performance; facilitating (positive) or debilitating (negative) effects. Unfortunately, previous studies on this issue show that language anxiety negatively affected students’ performance in most cases. This study aimed to find out the correlation between speaking anxiety and speaking performance in EFL context and investigating the major stressors of English speaking anxiety perceived by the students involved in this study. Mixed method was applied in this study. Then, three instruments were used to collect the data; a questionnaire named FLCAS (Foreign Language Classroom Anxiety Scale), an interview, and a speaking test. The finding showed that there was no significant relationship between speaking anxiety and speaking performance. Furthermore, based on the finding from FLCAS and interview, the major stressors of speaking anxiety perceived by the participants were resulting from comparing one’s speaking skill to others, getting a spontaneous question, being concerned if they were grammatically incorrect and used wrong pronunciation, not understanding what the teacher said, and being unable to convey something in the target language. These major stressors were basically stemmed from fear of negative evaluation and communication apprehension.